Using a multi-locational, longitudinal focus group method to conduct qualitative research into the role of public libraries - Appleton, Leo; Hall, Hazel (Qualitative and Quantitative Methods in Libraries; Vol 11 No 1 (2022): March issue 2022, 2022)
Introduction / Purpose  The purpose of this paper is to present the experiences of using a longitudinal focus group method in a library and information science research project. This was developed and used in a recent doctoral study about the role that public libraries in England and Scotland play within the information society. The research questions explored in the work focused on individual advantage accrued through using public libraries; the impact of public libraries on individual and community citizenship; and the role of the 21 st century public library. Design and approach At the outset of this study it was recognised that potential methods would need to enable dialogue with library users about their relationship with library service provision. Several qualitative methods were initially considered. These included ethnographic methods, naturalistic inquiry, grounded theory, Delphi methods, case studies, interviews and focus groups. Following evaluation, focus groups were deemed the most appropriate method for generating the required data.   Conducting the research  Up to ten library users at eight different public library locations across the United Kingdom took part in the study in three rounds over a period of three years between 2015 and 2018. At the focus group meetings the participants discussed and shared their experiences of using public libraries, and reflected upon how their library usage had affected them. Access to multiple participants allowed for elements of the research questions to be addressed in the course of an accessible and understandable conversations during which the participants spoke freely. The multi-location element allowed for a breadth of data to be generated, and the three rounds of focus groups added for depth.  Longitudinal studies are effective ways of observing and evidencing social development over time (Lewis & McNaughton Nicholls, 2013, 61-62) and this was a fundamental to the research. Here participants were able to reflect back on their most recent library usage from meeting to meeting, and to discuss this in a current and personal context. Findings The longitudinal focus group method had direct impact upon the quality of the data generated and the findings of the study. Whilst the paper will focus largely on the method, there will also be an opportunity to discuss some of the findings of the three phases of focus groups, which include: perceptions of the role of the library; the resilience of print; community ownership of libraries; enabling democracy and citizenship; social capital.   References  Lewis, J. and McNaughton Nicholls, C. (2013) “Design Issues” in J. Ritchie, J. Lewis, C. McNaughton Nicholls & R. Ormston (eds) Qualitative Research in Practice: a Guide for Social Science Students and Researchers . Los Angeles, Sage.